ANALISIS PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN PADA SEKRETARIAT DAERAH PEMERINTAH KABUPATEN TIMOR TENGAH SELATAN - Nesimnasi, Yabes Edison; Ga, Linda Lomi; Tungga, Cicilia A. (Universitas Nusa Cendana, 2023)
This study aims to obtain an overview of the implementation of financial SIMDA at the Regional Secretariat (SETDA) of the South Central Timor Regency Government, as well as to find out the causal factors that the Regional Secretariat has in implementing financial SIMDA, a well as the quality of information resulting from its implementation. Respondents in the study were 5 people consisting of Regional Secretariat employees, namely Administrative Section Employees, Accounting and Reporting Section Employees, Head of Finance and Reporting Sub Division and Section Head. Data were collected through direct interviews with respondents using interview guides, direct observation of the activities of the Regional Secretariat employees and documentation studies of related documents. The results of the interviews and the collected data were analyzed by descriptive method using a phenomenological approach. The results of the study indicate that in general the employees of the Regional Secretariat have understood the meaning of financial SIMDA and the description of its implementation related to input and output data. The factors possessed in implementing the implementation of SIMDA Finance are communication, human resources, attitude/disposition and bureaucratic structure, while the quality of information generated from the implementation of SIMDA Finance is reliable, but not timely and relevant.